Abdrücke von antiken und ausgewählten nachantiken Intagli und Kameen - Zwierlein-Diehl, Erika (Glaspasten im Martin von Wagner Museum der Universität Würzburg, 2023)
The collection comprises around 1500 glass pastes from the 18th to early 19th century. A first part with 946 glass pastes of antique gems from the 6th century BC to the 5th century AD and of such post-antique gems from the 15th to 18th centuries that are directly related to them is presented here.